Insurance Payor Status and Outcomes in Pediatric Sports-Related Injuries: A Rapid Review - Katherine M. Kutzer; Lulla V. Kiwinda; Daniel Yang; John Kyle Mitchell; Emily J. Luo; Emily J. Harman; Stephanie Hendren; Kendall E. Bradley; Brian C. Lau (Clinics and Practice)
Introduction: The rise in youth sports participation has led to an increase in pediatric sports-related injuries in the United States, contributing to growing healthcare costs and exacerbating socioeconomic disparities. Insurance payor status is a critical factor influencing access to care, treatment delays, and health outcomes. This study examines the association between insurance payor status and outcomes in pediatric sports-related injuries. Methods: A systematic review of the Medline database was conducted. Included studies reported insurance payor status and pediatric sports orthopedic patient outcomes following surgery. Outcomes included time to be seen by a provider, treatment access, complication and revision rates, postoperative Emergency Department (ED)/Urgent Care utilization, readmission rates, hospital length of stay, pain, functional scores, discharge destinations, return to activity, and follow-up. Results: A total of 35 studies comprising 535,891 pediatric patients were included. Publicly insured or uninsured patients consistently experienced significant delays in accessing care, with average wait times for clinic visits, imaging, and surgery up to six times longer compared to privately insured patients. These delays were associated with worsened injury severity, higher rates of postoperative complications, and poorer functional outcomes. Publicly insured patients were less likely to receive advanced treatments such as bracing or physical therapy, further compounding disparities. Minority groups faced delays even when controlling for insurance status. Conclusions: Public and uninsured pediatric patients face systemic barriers to timely and equitable care, resulting in worse outcomes following sports-related injuries. Future research should explore targeted solutions to ensure equitable care for this vulnerable population.